Quality of dental treatments under intravenous sedation among patients with disability: A self-matching study - Hsiu-Hsien Chen; Po-Yen Lin; Ching-Kai Lin; Le-Yin Hsu; Ming-Hua Hung; Ping-Yi Lin; Lin-Yang Chi (Elsevier, 2023)
Background/purpose: Patients with disabilities usually have difficulties in communication and mobility, and the quality of the dental treatments are often inferior. This study uses the Taiwan National Health Insurance Database to analyze the quality of dental treatment for patients with disabilities who receive intravenous sedation (IVS). Materials and methods: This study selected patients with disabilities who received dental treatment under IVS. Their oral cavity was divided into three major sections: anterior teeth, upper posterior teeth, and lower posterior teeth. Self-matching of the same section was conducted to observe whether operative dental treatment (OD) with or without IVS affected the occurrence of dental retreatment. This study observed the occurrence of refilling and the duration from the end of treatment until retreatment to compare treatment differences with or without IVS. Results: After self-matching, this study found 158 patients who received dental treatment within the same section with and without IVS. During a follow-up period of 17 years, 75.18% of the patients who received OD treatment required refilling, 10.87% required endodontic treatment, and 5.67% required tooth extraction. After OD treatment with IVS, the risks of refilling, endodontic treatment, and tooth extraction were 0.71 (95% CI: 0.58-0.87, P < 0.001), 0.77 (95% CI: 0.48-1.23, P = 0.28), and 0.64 (95% CI: 0.32-1.27, P = 0.20), respectively. Conclusion: For patients with disabilities, OD treatment with IVS significantly reduces the risk of refilling compared with OD treatment without IVS. IVS can be ideal for people with disabilities who receive dental treatment.